Comparison of the incidence of fetal prolonged deceleration after induction of labor analgesia between dural puncture epidural and combined spinal epidural technique: a pilot study - Shoko Okahara; Rie Inoue; Yumi Katakura; Hitomi Nagao; Saori Yamamoto; Shuko Nojiri; Jun Takeda; Atsuo Itakura; Hiroyuki Sumikura (BMC, 2023)
Abstract Background Abnormal cardiotocogram (CTG) tracing may appear after induction of neuraxial labor analgesia. Non-reassuring fetal status (NRFS) indicated by severely abnormal tracings, such as prolonged deceleration (PD) or bradycardia, can necessitate immediate operative delivery. Combined spinal epidural analgesia (CSEA) is known to result in more frequent abnormal tracings than epidural analgesia (EA); however, the corresponding data related to dural puncture epidural (DPE) are unclear. We aimed to evaluate the rates of incidence of severe abnormal CTG after induction of DPE and CSEA. Methods In this study of nulliparous women with full-term pregnancy, data for the DPE intervention group were prospectively collected, while those for the CSEA control group were obtained from medical records. Neuraxial analgesia was performed with cervical dilation ≤ 5 cm, administering initial epidural dosing of 15 mL of 0.125% levobupivacaine with fentanyl 2.5µg/mL for DPE, and intrathecal 0.5% bupivacaine 2.5 mg (0.5ml), fentanyl 10 µg (0.2ml), and 1.3 mL of saline for CSEA. The primary outcome was the incidence of PD, defined as a fetal heart rate reduction ≥ 15 bpm below the baseline and with a lowest value < 80 bpm, and lasting for ≥ 2 min but < 10 min (fetal heart rate < 80 bpm does not have to last for ≥ 2 min), within 90 min after induction of neuraxial labor analgesia. Results A total of 302 patients were analyzed, with 151 in each group. The incidence of PD after DPE induction was significantly lower than that after CSEA induction (4.0% vs. 14.6%, P = 0.0015, odds ratio = 0.243, 95% confidence interval = 0.095-0.617). Conclusion DPE appears to be a safer method compared to CSEA for neuraxial labor analgesia in the early stages of labor for nulliparous women. Trial registration UMIN-CTR: UMIN000035153 . Date registered: 01/01/2019.